ELK3 Mediated by ZEB1 Facilitates the Growth and Metastasis of Pancreatic Carcinoma by Activating the Wnt/β-Catenin Pathway - Zhao, Qiuyan; Ren, Yingchun; Xie, Haoran; Yu, Lanting; Lu, Jiawei; Jiang, Weiliang; Xiao, Wenqin; Zhu, Zhonglin; Wan, Rong; Li, Baiwen (Frontiers in Cell and Developmental Biology, 2021)
Rapid progression and metastasis are the major cause of death of pancreatic ductal adenocarcinoma (PDAC) patients. ELK3, a member of ternary complex factor (TCF), has been associated with the initiation and progression of various cancers. However, the role of ELK3 in PDAC need to be further elucidated. Online databases and immunohistochemistry were used to analyze ELK3 level in PDAC tissues. The function of ELK3 was confirmed by a series of in vivo and in vitro studies. Western blot and immunofluorescence were used to detect the molecular mechanisms in PDAC. ChIP-qPCR was used to study the mechanism responsible for elevation of ELK3 in PDAC. ELK3 level was higher in PDAC tissues than that in adjacent normal tissues. Functionally, we demonstrated that ELK3 acted as an oncogene to promote PDAC tumorigenesis and metastasis. Further investigations suggested that ELK3 could promote PDAC cells migration and invasion by activating Wnt/β-catenin pathway. Then we proved that ZEB1 could directly bind to the promoter of ELK3 to increase its transcription. Finally, both of them were associated with patients’ clinicopathological features and worse overall survival. Conclusively, our findings enrich the role of ELK3 in PDAC, and provide potential avenues for exploring more effective biomarkers and therapeutic strategies in the treatment of PDAC.